Dissecting Aneurysms of Posterior Cerebral Artery: Clinical Presentation, Angiographic Findings, Treatment, and Outcome - Taqi, Muhammad A.; Lazzaro, Marc A.; Pandya, Dhruvil J.; Badruddin, Aamir; Zaidat, Osama O. (Frontiers in Neurology, 2011)
Abstract: Background: The dissecting posterior cerebral artery (PCA) aneurysms are very rare. These aneurysms pose significant treatment challenge and need careful evaluation to formulate an optimal treatment plan in case of ruptured or un-ruptured presentations. Methods: Retrospective review of a prospectively collected data. Results: 7 patients with dissecting aneurysms of the PCA were identified. Six out of seven presented with subarachnoid hemorrhage (SAH) and one with ischemic stroke (IS). 3/7 were treated with endovascular coil embolization without sacrifice of the parent artery and the rest had parent artery occlusion (PAO) with coil embolization. None of the patients developed new neurological deficits post procedure. Aneurysm re-occurred in 2 patients that were treated without PAO. Conclusion: Endovascular treatment of the dissecting PCA aneurysm is safe and feasible. It can be performed with or without PAO. Recurrence is more common without PAO and close follow-up is warranted.